A LITERATURA COMPARADA NO BRASIL - Bittencourt, Gilda (Organon, 2012)
Comparatism followed the steps of Brazilian literatureinvestigation even before the establishment of Comparative Literature as asistematic study, for it was a spontaneous practice which was present in thecritical essays by different scholars. Comparative Literature has beenintroduced in Brazilian University from the 30's onwards. The name ofAntonio Candido de Mello e Souza has contributed to its development andconsolidation, mainly through his renewed ideas of the concept of influence.His critical discourse was the starting point for the search of a decolonizedcomparativist model. The establishment of graduate courses in ComparativeLiterature on a regular basis has given a great impetus to the field in Brazil,producing in-depth studies which have shown the interliterary relationsthrough a new point of view, breaking with the tradicional concepts of debtsand influences. The ripening of Comparative Literature in Brazil can bemeasured by the creation of the National Association (ABRALIC) in 1986,and by the realization of four National Conferences.